Simulasi dan Pendampingan, Pengelolaan serta Pelaporan Keuangan Badan Usaha Milik Desa (BUMDes) di Wilayah Kecamatan Cimenyan Kabupaten Bandung - Perdana Wahyu Santosa; Hesty Juni Tambuati Subing; Harry Budiantoro; Khairul Shaleh; Cahyani Rahma Noviyanti (LPMP Imperium, 2024)
Village-owned enterprises (BUMDes) in Cimenyan Sub-district, Bandung Regency, manage several businesses operated by the local community. In its development, financial management in BUMDes is still simple. The lack of understanding of BUMDes managers resulted in a lack of integration in the bookkeeping of transactions. The PKM team from FEB Yarsi University made this training which was held on Tuesday, May 21, 2024 which was attended by all management staff totaling 14 people with the aim that BUMDes Management and the business units involved can prepare financial reports based on SAK ETAP. The method used is the Participatory Action Research (PAR) method, which involves all parties actively in reviewing ongoing actions. The results of this PKM show that the Pre test is 53% while after carrying out the training the Post test results are 91%, which means that there is an increase in the knowledge of BUMDes devices where almost all of them have understood village financial reports. This simple financial report management training was carried out well, and it is hoped that BUMDes administrators can apply simple financial management and reporting knowledge that is in accordance with applicable regulations, transparent, and accountable.